2012
DOI: 10.1002/pssc.201200546
|View full text |Cite
|
Sign up to set email alerts
|

Silicon micropillars: high stress plasticity

Abstract: Silicon micropillars obtained by FIB from Floating Zone silicon single crystal have been deformed in situ in a SEM between room temperature and 400 °C. Pillars with <123> axis were studied in order to promote single slip deformation. Mechanical data as a function of pillar diameter and surface deformation microstructures observed by SEM are reported. Yield stresses as a function of temperature are compared with those resulting from high‐pressure tests (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 10 publications
5
25
0
Order By: Relevance
“…[2,[21][22][23][24][25][26][27][28][29][30][31][32] A selection of materials thus studied in terms of their plasticity is shown in Fig. 2, while Figs.…”
Section: Investigating Plasticity In Hard Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,[21][22][23][24][25][26][27][28][29][30][31][32] A selection of materials thus studied in terms of their plasticity is shown in Fig. 2, while Figs.…”
Section: Investigating Plasticity In Hard Crystalsmentioning
confidence: 99%
“…Among the systems, which have been studied to date by research groups around the globe are Cu-Sn phases (solders), carbides and nitrides, MAX phases, binary nickel and iron aluminides, metallic and silicate glasses, high entropy alloys and quasicrystals, [2,[21][22][23][24][25][26][27][28][29][30][31][32]36,[44][45][46][47][48] see also Fig. 2.…”
Section: Investigating Plasticity In Hard Crystalsmentioning
confidence: 99%
“…In terms of the activation volume, V*, there does appear to be such a transition which may correlate to such a change from velocity to nucleation control. For submicron sizes, we and others 214 have shown that the activation volume approaches 1 b 3 as shown in Fig. 5.…”
mentioning
confidence: 52%
“…In particular, the bending deformation will promote the propagation of any cracks due to defects in the tension side of the cantilever induced in the manufacture process. Rabier et al 32 looked at several different sized micropillars manufactured by FIB machining, oriented in a h123i direction to ensure single-slip system activation. Again, larger pillars (2000-nm diameter) showed cracking and splitting, whereas smaller pillars (980 nm diameter) showed plastic flow even at room temperature.…”
Section: Bend Tests In Siliconmentioning
confidence: 99%